Audiological characteristics of children with congenital unilateral hearing loss: insights into Age of reliable behavioural audiogram acquisition and change of hearing loss - Zhang, Vicky W.; Hou, Sanna; Wong, Angela; Flynn, Christopher; Oliver, Jane; Weiss, Michelle; Milner, Stacey; Ching, Teresa Y. C. (Frontiers in Pediatrics, 2023)
This study aimed to report the audiological characteristics of children with congenital unilateral hearing loss (UHL), examine the age at obtaining the first reliable behavioural audiograms, and investigate hearing changes from diagnosis at birth to the first reliable behavioural audiogram. This study included 91 children diagnosed with UHL via newborn hearing screening and had reliable behavioural audiograms before 7 years of age. Information about diagnosis, audiological characteristics and etiology were extracted from clinical reports. Analyses were conducted to explore the potential reasons influencing the age at obtaining the first reliable behavioural audiograms, and hearing changes at octave frequencies (0.5-4 kHz). The proportions of hearing change and the clinical characteristics of children with and without hearing deterioration, were described using two definitions: 1: a decrease of ≥10 dB at ≥ 2 adjacent frequencies between 0.5 and 4 kHz, or a decrease of ≥15 dB at one octave frequency in the same frequency range. 2: a change of ≥20 dB in the average of pure-tone thresholds at 0.5, 1, and 2 kHz. Results showed 48 children (52.7%) had first reliable behavioural audiogram by 3 years of age (mean: 3.0; SD: 1.4; IQR: 1.8, 4.1). We found a significant association between children's behaviour and middle ear issues in relation to delayed reliable audiogram. When comparing initial diagnosis hearing thresholds with the first reliable behavioural audiogram, majority of children experienced deterioration rather than improvement at each frequency, particularly at 0.5 and 1 kHz. 71 children had hearing deterioration between the diagnosis and the first behavioural audiogram at one or more frequencies (0.5-4 kHz), with 52 of them (73.2%) developing severe to profound hearing loss. When using the averaged three frequency thresholds (definition 2), only 26.4% (n= 24) in the sample were identified as having hearing deterioration. The study also reported diverse characteristics of children with or without hearing deterioration. The finding highlights the importance of monitoring hearing threshold levels after diagnosis, so that appropriate intervention can be implemented in a timely manner. For clinical management, deterioration of 15 dB at one or more frequencies that does not recover warrants action.